El Modelo Kaizen en el sector público - Casanova-Villalba, César (Editorial Grupo AEA, 2022)
Public sector institutions must meet the needs of their users, which is why they are controlled by different governmental entities and comply with different legal regulations. Under this approach different methodologies for efficiency and effectiveness arise, the book responds to a "Kaizen" model but under the governmental methodology of Government by Results. The model presented uses quality tools such as identification of the mudas that correspond to waste, application of the 5s, which is a methodology applied to cleanliness, order, planning, safety and self-discipline, these two tools under a PHVA scheme that is nothing more than the process of planning, doing, verifying and acting. In order to apply this model, data must be obtained from the processes and activities, with which we have a background and can measure the fulfillment of institutional objectives.